Advances in Mechanical Engineering and Mechanics Selected Papers from the 4th Tunisian Congress on Mechanics, CoTuMe 2018, Hammamet, Tunisia, October 13-15, 2018 - Benamara, Abdelmejid; Haddar, Mohamed; Tarek, Benameur; Salah, Mezlini; Fakher, Chaari; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book reports on original theoretical and experimental findings related to a number of cutting-edge topics in mechanics and mechanical engineering, such as structure modelling and computation; design methodology and manufacturing processes; mechanical behaviour of materials; fluid mechanics and energy; and heat and mass transfer. It includes a selection of papers presented at the 4th Tunisian Congress on Mechanics, CoTuMe'2018, held in Hammamet, Tunisia, on October 13-15, 2018. Thanks to the good balance of theory and practical findings, it offers a timely snapshot for researchers and industrial communities alike, and a platform to facilitate communication and collaboration between the two groups.
Bone Remodeling after Total Hip Arthroplasty - Numerical Calculation and Clinical Validation with DEXA Investigations -- Intelligent neural network control for active heavy truck suspension -- Analytical modeling of the tool trajectory with local smoothing -- Repairing Cracked Structures Using the IF Process -- Stochastic design of non-linear electromagnetic vibration energy harvester -- Mechanical characterization of coating materials based on nanoindentation technique -- An inverse calculation of local elastoplastic parameters from instrumented indentation test -- Finite element simulation of single point incremental forming process of aluminum sheet based on non-associated flow rule.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Materials -- Analysis; Engineering design; Multibody Systems and Mechanical Vibrations; Characterization and Analytical Technique; Engineering Design